Antenna in 6G wireless communication system: specifications, challenges, and research directions - Hajiyat, Zahraa Raad Mayoof; Ismail, Alyani; Sali, Aduwati; Hamidon, Mohd Nizar (Elsevier, 2021)
The Terahertz (THz) frequency band (0.1-10 THz) will be used in the 6G wireless communication system to support the user demand of higher data rates and ultra-high-speed communication for many future applications. In this paper, 6G antenna specifications for these applications are highlighted. An exhaustive review of recent related-works of THz band antenna, fabrication and measurement are presented. Challenges of the THz band antenna design, fabrication and measurement are addressed. Research directions of THz band antenna for 6G technology are included, for THz band in antenna design, manufacturing and testing.